2015
DOI: 10.1080/10420150.2015.1010170
|View full text |Cite
|
Sign up to set email alerts
|

Low and moderate dose gamma-irradiation and annealing impact on electronic and electrical properties of AlGaN/GaN high electron mobility transistors

Abstract: 2015): Low and moderate dose gamma-irradiation and annealing impact on electronic and electrical properties of AlGaN/GaN high electron mobility transistors, Radiation Effects and Defects in Solids: Incorporating Plasma Science and Plasma Technology,To understand the effects of 60 Co gamma-irradiation, systematic studies were carried out on n-channel AlGaN/GaN high electron mobility transistors. Electrical testing, combined with electron beam-induced current measurements, was able to provide critical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The generated defects are supposed to be nitrogen vacancies (VN), which act as donors in gallium nitride. Conflicting results have been reported, indicating instead a reduction in current [593], [594]. The difference may originate from different device structure and quality, or from the impact of different dose levels, showing improvements at lower dose and damage at high dose.…”
Section: Gamma Ray Irradiationmentioning
confidence: 97%
“…The generated defects are supposed to be nitrogen vacancies (VN), which act as donors in gallium nitride. Conflicting results have been reported, indicating instead a reduction in current [593], [594]. The difference may originate from different device structure and quality, or from the impact of different dose levels, showing improvements at lower dose and damage at high dose.…”
Section: Gamma Ray Irradiationmentioning
confidence: 97%
“…21,29,30,34 The activation energies observed from EBIC studies were regarded as due to V N for low doses. The enhancement of device function at low doses extended to dc properties as well, including transconductance, I DS magnitudes, and gate leakage currents.…”
Section: Discussionmentioning
confidence: 99%
“…28 This was coupled with EBIC for determination of L and its associated activation energy as a function of gamma irradiation dose in Ref. 29. The thermal activation energy found initially near 80 meV reduced for doses of 50 and 300 Gy while L was increased, while the opposite trend is observed for doses greater than 300 Gy.…”
mentioning
confidence: 99%
“…Studies have reported both improvements and degradation in material properties following c-ray irradiation. [9][10][11][12][13][14][15][16] Membreno et al 17 reported the effect of cirradiation on n-GaN material through transient capacitance measurements. The generation of two defect levels with thermal activation energies of 89 meV and 132 meV, respectively, was reported after the material was subjected to a c-irradiation dose of 210 kGy.…”
Section: Introductionmentioning
confidence: 99%
“…GaN high electron mobility transistors (HEMTs) exhibit a decrease in gate leakage current with an increase in transconductance after being subjected to a low c-ray dose of 300-500 Gy. 12,14,20 Aktas et al 8 reported an increase in the transconductance of GaN HEMTs with a À 0.1 V shift in their threshold voltage even at the very high c-ray dose of 6 MGy. By contrast, Jha et al 11 reported a decrease in the transconductance of GaN HEMT devices after they were subjected to c-irradiation doses of up to 100 kGy.…”
Section: Introductionmentioning
confidence: 99%